Current practice patterns and patient persistence with anticoagulant treatments for cancer‐associated thrombosis. Issue 1 (30th May 2017) - Khorana, Alok A.; McCrae, Keith R.; Milentijevic, Dejan; Fortier, Jonathan; Nelson, Winnie W.; Laliberté, François; Crivera, Concetta; Lefebvre, Patrick; Yannicelli, Daniel; Schein, Jeff
Abstract: Background: Recommended therapeutic options for the management of venous thromboembolism (VTE) in patients with cancer are burdensome, and compliance with guidelines is unknown. Objectives: To describe current treatment patterns and to evaluate patient persistence on various anticoagulants. Patients/Methods: Medical and pharmacy claims from the Humana Database were analyzed (01/2007‐12/2014). Newly diagnosed cancer patients treated with anticoagulants were categorized into one of the following cohorts: low–molecular‐weight heparin (LMWH), warfarin, and rivaroxaban. Discontinuation, switching, and persistence with the index therapy were analyzed. Results: A total of 2941 newly diagnosed patients with cancer who developed VTE and received anticoagulation in outpatient settings were identified. Of these, 97% initiated anticoagulation with LMWH (n=735; 25%), warfarin (n=1403; 47.7%), or rivaroxaban (n=709; 24.1%). Median treatment durations for the LMWH, warfarin, and rivaroxaban cohorts were 3.3, 7.9, and 7.9 months, respectively; Kaplan‐Meier rates of persistence to the initial therapy were 37%, 61%, and 61% at 6 months. Warfarin and rivaroxaban users were significantly more likely to remain on initial therapy compared to LMWH (adjusted hazard ratios [HRs; 95% CI]: warfarin, 0.33 [0.28‐0.38]; rivaroxaban, 0.38 [0.32‐0.46]). The proportion of patients that switched from their initial treatment to another anticoagulation treatment was 22.9%, 7.9%, and 4.7% in the LMWH, warfarin, and rivaroxaban cohorts, respectively. Conclusions: This real‐world analysis showed that, despite guideline recommendations, warfarin and rivaroxaban are at least as equally utilized as LMWH for the treatment of cancer‐associated thrombosis. LMWH was associated with significantly lower persistence, shorter duration of treatment, and more switching than warfarin and rivaroxaban.